TAK1 mediates apoptosis via p38 involve in ischemia-induced renal fibrosis. (31st October 2018) - Zhou, Jun; Zhong, Jiying; Huang, Zhenxing; Liao, Meijuan; Lin, Sen; Chen, Jia; Chen, Hongtao
Abstract: Renal fibrosis is a common and characteristic symptom of chronic kidney disease (CKD). However, the molecular mechanisms of renal fibrosis remain elusive. Ischemia injury, as a major cause of AKI, deserves more attention in order to improve the knowledge of AKI-induced fibrosis. Transforming growth factor-β (TGF-β)-activated kinase 1 (TAK1) interacts directly with TGF-β, which play a critical role in the progression of fibrosis. Therefore, the present study aimed to investigate the role of TAK1 in the pathogenesis of ischemia-induced renal fibrosis. Compared with mice in the vehicle group, mice intraperitoneally injected with TAK1 inhibitor were found to have lower serum creatinine, less tubular damage and more mild fibrosis following ischemia-induced AKI. Furthermore, inhibition of TAK1 reduced p38 phosphorylation, decreased expression of Bax and caspase 3 and apoptosis cells in kidneys of mice treated with IR-induced AKI. Compared with vehicle-treated renal tubular epithelial cells, TAK1 overexpression cells were found to have a higher apoptosis and fibrosis index level and p38 phosphorylation following hypoxia/reoxygenation (H/R) treatment. Furthermore, the p38 inhibitor combined with TAK1 overexpression verified the role of TAK1/p38 signaling pathway in apoptosis and fibrosis index level of renal tubular epithelial cells treated with H/R. Thus, our results show that TAK1 plays an important role in the pathogenesis of ischemia-induced renal fibrosis and may mediate p38-regulated cell apoptosis.